Crystallographic and spectroscopic investigations on oxidative coordination in the heteroleptic mononuclear complex of cerium and benzoxazine dimer - Worawat Wattanathana (2022)
Among lanthanide-based compounds, cerium compounds exhibit a significant role in a variety of research fields due to their distinct tetravalency, high economic feasibility, and high stability of Ce(IV) complexes. Herein, a systematic investigation of crystallographic information, chemical properties, and mechanistic formation of the novel Ce(IV) complex synthesized from cerium(III) nitrate hexahydrate and 2,2′-(methylazanediyl)bis(methylene)bis(4-methylphenol) (MMD) ligand has been explored. According to the analysis of the crystallographic information, the obtained complex crystal consists of the Ce(IV) center coordinated with two nitrate ligands and two bidentate coordinated (N-protonated and O,O-deprotonated) MMD ligands. The fingerprint plots and the Hirshfeld surface analyses suggest that the C–H· · · O and C–H· · · π interactions significantly contribute to the crystal packing. The C–H· · · O and C–H· · · π contacts link the molecules into infinite molecular chains propagating along the [100] and [010] directions. Synchrotron powder X-ray diffraction (XRD) and X-ray absorption spectroscopy (XAS) techniques have been employed to gain an understanding of the oxidative complexation of Ce(IV)-MMD complex in detail. This finding would provide the possibility to systematically control the synthetic parameters and wisely design the precursor components in order to achieve the desired properties of novel materials for specific applications.